The interactive effect of endogenous and exogenous institutions on forest use practices in socio-culturally diverse landscapes of Cameroon - Alfred Kechia Mukong; Jude Ndzifon Kimengsi; Constantine Nwune Alusoh (Environment, Development and Sustainability, 2023)
In resource-dependent communities of sub-Saharan Africa, it is widely held that endogenous institutions either countervail or complement exogenous institutions, indicating inconsistency in empirical evidence. This has re-ignited interest to establish the independent and/or interactive effect of both endogenous and exogenous institutional structures. This paper quantitatively analyses the independent and interactive effects of community-based (endogenous) and state-based (exogenous) forest management institutions (FMIs) on the exploitation of forest resources, drawing from a representative sample of 446 households from three socio-culturally diverse landscapes of Cameroon. The paper introduces a multiplicative interaction term and used the heteroscedasticity-based instrumental variables approach to estimate the direct and indirect effects of exogenous and endogenous institutions on the behaviour of users of forest-based resources. The results indicate that: (i) Both exogenous structures of FMIs and the interaction term significantly constrain the extractive behaviour of forest resource users; (ii) endogenous structures and not rules are vital in improving the role of exogenous structures in forest resource management; (iii) while traditional rules are less significant in shaping forest resource exploitation, their effectiveness is highly significant across the study sites and (iv) institutional compatibility and complementarity was observed in landscapes that were formerly shaped by British colonial influence (Bakossi and Kilum-Ijim). This paper does not only establish the relative influence of exogenous and endogenous FMIs, it also highlights future research pathways on institutional change in the context of environmental resource management in sub-Saharan Africa.
Keywords: 330; Institutions; Interactions; Forest resources; Compatibility; Complementarity